Sistem Pakar Deteksi Gangguan Jaringan Komputer Pada Jaringan LAN Menggunakan Metode Forward Chaining - videl kobak; Adi Israel W.C.R Peday; Astrin Aprilia Umasugi; Juan Philbert Artori Kris; Patmawati Hasan (CV Edujavare Publishing, 2026)
Local Area Network (LAN) network disruptions in vocational education environments often hamper the learning process and student practicums, primarily due to limited technicians and the low basic troubleshooting skills of both teachers and students. This research aims to design and implement a web-based expert system for diagnosing LAN network disruptions using the forward chaining method. This method was chosen because of its data-driven nature, where reasoning begins with user-inputted symptoms and leads to conclusions about the type of disruption and repair solutions. The system's knowledge base was built from observations and interviews with technicians, covering 18 symptoms and four main types of disruptions: network cable unplugged, IP address conflict, destination host unreachable, and request timeout. Testing was conducted on 30 real-world cases in a computer laboratory, comparing the system's diagnostic results with those of experts. The test results demonstrated an accuracy rate of 93.33%, with positive responses from teachers and students regarding the system's ease of use. These findings demonstrate that the developed expert system can accelerate the diagnostic process, reduce reliance on technicians, and maintain the continuity of LAN network practicums in ICT-based vocational schools.